1993
DOI: 10.1111/j.1432-1033.1993.tb17607.x
|View full text |Cite
|
Sign up to set email alerts
|

Purification, characterization and HPLC assay of Salmonella glucose‐1‐phosphate thymidylyltransferase from the cloned rfbA gene

Abstract: We here report on the purification and characterization of glucose-1-phosphate thymidylyltransferase, the first of four enzymes commited to biosynthesis of dTDP-L-rhamnose from Salmonella enterica strain LT2. The purification was greatly facilitated by the cloning of the IjhA gene encoding this enzyme. Pure enzyme was obtained by 109-fold enrichment in three chromatography steps.The glucose-1 -phosphate thymidylyltransferase catalyzes a reversible bimolecular group transfer reaction and kinetic measurements in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
60
1

Year Published

1994
1994
2009
2009

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(66 citation statements)
references
References 15 publications
5
60
1
Order By: Relevance
“…The genes encoding the first two enzymes in the pathway, rmfA (a-D-glucose-1-phosphate thymidylyltransferase) and rmlB (dTDP-~-glucose-4',6'-dehydratase) have been cloned and expressed from several different organisms (Ma et al, 1997;Lindquist et al, 1993;Romana et af., 1991;Marumo et al, 1992) and shown to catalyse the expected reactions shown in Fig. 1.…”
Section: Introductionmentioning
confidence: 99%
“…The genes encoding the first two enzymes in the pathway, rmfA (a-D-glucose-1-phosphate thymidylyltransferase) and rmlB (dTDP-~-glucose-4',6'-dehydratase) have been cloned and expressed from several different organisms (Ma et al, 1997;Lindquist et al, 1993;Romana et af., 1991;Marumo et al, 1992) and shown to catalyse the expected reactions shown in Fig. 1.…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis of thymidine diphosphate (dTDP) 1 -L-rhamnose, which is the activated nucleotide sugar form of L-rhamnose, has been well studied by several investigators (15)(16)(17)(18). The anabolism of dTDP-L-rhamnose from D-glucose-1-phosphate is catalyzed by four enzymes, namely, D-glucose-1-phosphate thymidylyltransferase, dTDP-D-glucose 4,6-dehydratase, dTDP-4-keto-6-deoxy-D-glucose 3,5-epimerase, and dTDP-4-keto-L-rhamnose reductase ( Fig.…”
mentioning
confidence: 99%
“…The anabolism of dTDP-L-rhamnose from D-glucose-1-phosphate is catalyzed by four enzymes, namely, D-glucose-1-phosphate thymidylyltransferase, dTDP-D-glucose 4,6-dehydratase, dTDP-4-keto-6-deoxy-D-glucose 3,5-epimerase, and dTDP-4-keto-L-rhamnose reductase ( Fig. 1) (15)(16)(17)(18). On the other hand, D-fucose has been identified as a component of other bacterial polysaccharides in only a few publications (19,20), and there is no report concerning the activated nucleotide sugar form of D-fucose in the synthesis of dTDP-D-fucose.…”
mentioning
confidence: 99%
“…HPLC on SAX anion-exchange columns have earlier been successfully used for assays of the enzymes coded by the Salmonella genes r -A [28], @CD [lo] and r@F [20], and have also been used in studies on the biosynthesis of CDP-D-abequose from CDP-D-glucose, but the CDP-sugars were not resolved under the conditions used [26]. This is the first time, to our knowledge, that CDP-D-abequose has been synthesised vitro in quantitatively significant amounts, and that product as well as the intermediates have been entirely identified.…”
Section: Discussionmentioning
confidence: 99%